The Battles of Kings Mountain and Cowpens : the American Revolution in the Southern Backcountry. - Walker, Melissa A. (Critical moments in American history., 2013)
The American South is so identified with the Civil War that people often forget that the key battles from the final years of the American Revolution were fought in Southern states. The Southern backcountry was the center of the fight for independence, but backcountry devotion to the Patriot cause was slow in coming. Decades of animosity between coastal elites and backcountry settlers who did not enjoy accurate representation in the assemblies meant a complex political and social milieu throughout this turbulent time. The Battles of Kings Mountain and Cowpens br.